(untitled) (Perner’s Contacts, 2017)
The paper deals with the implementation of the selected Theory of Constraints technique in order to identify the main causes of undesirable consequences in the field of inventory logistics. The need to identify the undesirable consequences of inventory logistics is primarily related to the negative impact on the costs system, profitability and quality of the entire supply chain. Implementation issues especially deal with the individual steps of the process related to the creation of the Theory of Constraints particular tree (technique). The intention of the technique is to identify the main causes that have the most significant impact on side effects of supplying on supply chain.